Prevalence estimates of major depressive disorder in 27 European countries from the European Health Interview Survey: accounting for imperfect diagnostic accuracy of the PHQ-8 - Andrea Benedetti; Brooke Levis; Brett Thombs; Geraldine Rauch; Matthias Rose; Polychronis Kostoulas; Dario Zocholl; Felix Fischer (BMJ Mental Health, 2023)
Background Cut-offs on self-report depression screening tools are designed to identify many more people than those who meet criteria for major depressive disorder. In a recent analysis of the European Health Interview Survey (EHIS), the percentage of participants with Patient Health Questionnaire-8 (PHQ-8) scores ≥10 was reported as major depression prevalence.Objective We used a Bayesian framework to re-analyse EHIS PHQ-8 data, accounting for the imperfect diagnostic accuracy of the PHQ-8.Methods The EHIS is a cross-sectional, population-based survey in 27 countries across Europe with 258 888 participants from the general population. We incorporated evidence from a comprehensive individual participant data meta-analysis on the accuracy of the PHQ-8 cut-off of ≥10. We evaluated the joint posterior distribution to estimate the major depression prevalence, prevalence differences between countries and compared with previous EHIS results.Findings Overall, major depression prevalence was 2.1% (95% credible interval (CrI) 1.0% to 3.8%). Mean posterior prevalence estimates ranged from 0.6% (0.0% to 1.9%) in the Czech Republic to 4.2% (0.2% to 11.3%) in Iceland. Accounting for the imperfect diagnostic accuracy resulted in insufficient power to establish prevalence differences. 76.4% (38.0% to 96.0%) of observed positive tests were estimated to be false positives. Prevalence was lower than the 6.4% (95% CI 6.2% to 6.5%) estimated previously.Conclusions Prevalence estimation needs to account for imperfect diagnostic accuracy.Clinical implications Major depression prevalence in European countries is likely lower than previously reported on the basis of the EHIS survey.